Dispersant suitable for wide temperature range nanometer lithium iron phosphate positive electrode slurry and preparation method and application thereof
Patent Information
- Application Number
- CN202611175157.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-16
AI Technical Summary
然而,该分散剂的亲溶剂链段(N-乙烯基吡咯烷酮)与溶剂之间的亲和力仍有提升空间,且其分散作用机理主要依赖于分子链的双亲性,缺少明确的多重协同分散机制
本发明提供的不是简单的三元共聚物,而是“锚固-电荷-位阻”三种功能单体的分子级协同设计,锚固保证分散剂在颗粒表面牢固吸附不脱附,电荷提供强静电排斥力抵抗电解质干扰,位阻形成物理屏障防止颗粒靠近——三者缺一不可,共同实现对纳米磷酸铁锂的高效、稳定分散。
Smart Images

Figure CN122917232A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a dispersant suitable for wide-temperature-range nano-lithium iron phosphate cathode slurry, its preparation method, and its application. Background Technology
[0002] Lithium iron phosphate (LiFePO4) batteries benefit from the unique olivine structure of their cathode material, which exhibits low strain during electrochemical cycling and maintains good cycle stability. This material is widely available, environmentally friendly, and boasts long cycle life and high safety, making it widely used in the new energy vehicle sector. Reducing the particle size of the phosphate cathode material can shorten the cycle time of LiFePO4 batteries. + Diffusion pathway. Therefore, the small size effect of nanoscale lithium iron phosphate (LiFePO4) is proposed to enhance the diffusion path of Li. + Migration rate, the electrolyte can make full contact with it.
[0003] LiFePO4 has a small particle size (D50 of approximately 0.2-2 μm) and a large specific surface area. During slurry preparation, it adsorbs a significant amount of NMP, requiring more PVDF. Furthermore, NMP needs to be added later to adjust viscosity, leading to a low solids content in the slurry. This low solids content has several drawbacks. More solvent needs to be evaporated during coating and drying, reducing the coating rate and increasing equipment energy consumption. In severe cases, it can cause edge curling, electrode cracking, and binder floating, resulting in electrode scrap and even affecting battery safety. Moreover, as a non-Newtonian liquid, the high specific surface area of the nanoparticles leads to van der Waals effects and electrostatic repulsion, potentially causing LiFePO4 agglomeration, which may be counterproductive. High-speed mechanical stirring and ultrasonic stirring are commonly used to improve slurry stability, but experiments have shown that when the external mechanical force is removed, the particles in the slurry will re-agglomerate due to Brownian motion. Excessive dispersion intensity can also damage the material structure, breaking its molecular chains and causing it to lose its original molecular structure, leading to binder failure. Therefore, how to increase the solid content of cathode slurry while ensuring good dispersion has always been a technical problem that needs to be solved in this field.
[0004] Adding dispersants to the cathode slurry is a common method to improve dispersion. Currently used dispersants mainly include polyvinylpyrrolidone (PVP) and polyacrylamide (PAM). However, these dispersants require a relatively large amount to achieve good dispersion, which significantly reduces the mass ratio of the cathode active material in the cathode material layer, thereby reducing the specific capacity of the battery.
[0005] Therefore, those skilled in the art are dedicated to developing novel dispersants to achieve excellent dispersion effects with lower dosages. For example, Chinese patent CN114583163B discloses a dispersant for lithium-ion batteries, which includes N-derived nitrogen... The dispersant comprises structural unit A (derived from conjugated diene monomers), structural unit B (derived from organic acid monomers), and structural unit C (derived from organic acid monomers). It achieves an amphiphilic dispersion effect through the solubility provided by the N-vinylpyrrolidone structural unit, the molecular chain flexibility provided by the conjugated diene structural unit, and the affinity for the surface of the positive electrode active material provided by the organic acid structural unit. However, the affinity between the solubility segment (N-vinylpyrrolidone) and the solvent in this dispersant still has room for improvement, and its dispersion mechanism mainly relies on the amphiphilicity of the molecular chain, lacking a clear multiple synergistic dispersion mechanism.
[0006] Furthermore, existing dispersants generally lack sufficient dispersion stability over a wide temperature range, making it difficult to meet the process requirements and performance demands of lithium-ion batteries under different temperature conditions. Therefore, developing a novel dispersant that combines high dispersion efficiency, low addition amount, and wide temperature range adaptability is of significant practical importance. Summary of the Invention
[0007] The present invention aims to provide a dispersant suitable for wide-temperature-range nano-lithium iron phosphate cathode slurry, so as to improve the dispersibility and solid content of the cathode slurry, achieve stable dispersion under wide-temperature conditions, and avoid the problem of reduced battery specific capacity caused by the decrease in cathode active material content.
[0008] In a first aspect, to achieve the above objectives, the present invention adopts the following technical solution: a dispersant suitable for wide-temperature-range nano-lithium iron phosphate cathode slurry, wherein the dispersant comprises a ternary dispersant and an initiator composed of itaconic acid imine, 2-acrylamide-2-methylpropanesulfonic acid and methoxy polyethylene glycol acrylate.
[0009] Preferably, as an improvement, the initiator is ammonium persulfate.
[0010] Preferably, as an improvement, the itaconic acid imine, 2-acrylamide-2-methylpropanesulfonic acid, 42-52 parts of methoxy polyethylene glycol acrylate, and 1-1.5 parts of ammonium persulfate are present by weight fraction.
[0011] Preferably, as an improvement, the dispersant is a light brown transparent solution with a solid content of 28% to 35%.
[0012] Secondly, the present invention provides a method for preparing the above-mentioned dispersant, wherein itaconic acid imine and 2-acrylamide-2-methylpropanesulfonic acid are dissolved in water and stirred until completely dissolved, the pH is adjusted to 3-4, the temperature is raised to 65-75°C, and then a mixed solution of methoxy polyethylene glycol acrylate and ammonium persulfate is added dropwise. After the reaction is completed, the pH is adjusted to 6-7 to obtain the dispersant.
[0013] Preferably, as an improvement, when adding the mixed solution of methoxy polyethylene glycol acrylate and ammonium persulfate, the dropping time is controlled to be 2.5~3.5h.
[0014] Preferably, as an improvement, the solution used to adjust the pH to 6-7 is a 15% NaOH solution.
[0015] Thirdly, the dispersant described above in this invention is used in the preparation of positive electrode slurry for lithium iron phosphate batteries.
[0016] Fourthly, a positive electrode slurry is provided, comprising the dispersant described above.
[0017] This invention addresses the dispersion requirements of nano-lithium iron phosphate, combining the core logic of "strong anchoring, high charge, and excellent steric hindrance." It uses a ternary dispersant composed of itaconic acid imine (IAI), 2-acrylamide-2-methylpropanesulfonic acid (AMPS), and methoxy polyethylene glycol acrylate (MPEG-AA). Its core structure features a synergistic effect of "anchoring-charge-steric hindrance" through an imine anchoring group, a sulfonic acid charge layer, and a polyether chain segment steric hindrance layer. The working principle is as follows: Anchoring monomer—Itaconic acid imine (IAI): Continuing the function of the core imide group (-CONH-), it forms multi-point strong adsorption with the hydroxyl groups on the surface of nano-lithium iron phosphate through hydrogen bonds and coordination bonds. The anchoring strength is improved by more than 25% compared with ordinary sulfonic acid dispersants, avoiding the dispersant's tendency to adhere to high Li- concentrations. + Desorption in concentrated slurry.
[0018] Charged monomer—2-acrylamide-2-methylpropanesulfonic acid (AMPS): The core provides sulfonic acid groups (-SO3H), which are neutralized to form sodium sulfonate (-SO3Na). Compared with systems such as carboxylate salts, the sulfonic acid groups have a lower pKa (about 1.2), which can be completely dissociated in acidic / neutral slurries to form a more stable negative charge layer, improving the resistance to electrolyte interference by 40%.
[0019] This avoids secondary aggregation caused by charge shielding. Simultaneously, the amide groups in the AMPS molecule can assist in the adsorption of imide groups, increasing the binding force with the particle surface.
[0020] Steric hindered monomer – methoxy polyethylene glycol acrylate (MPEG-AA): The side chain retains polyether segments (molecular weight 1000~1500), which are fully extended in organic (NMP) or aqueous systems to form a 10~14nm steric hindered layer. The high hydrophilicity and hydrophobicity matching between the polyether chain and the sulfonic acid group can reduce chain entanglement and further reduce the viscosity of the slurry.
[0021] Initiator – Ammonium persulfate (APS): Matches the reactivity of AMPS, avoids uneven chain segment distribution caused by excessively rapid polymerization, and ensures uniform grafting of the three types of monomers.
[0022] The beneficial effects of this invention are: This invention does not provide a simple ternary copolymer, but a molecular-level synergistic design of three functional monomers: "anchoring, charge, and steric hindrance." Anchoring ensures that the dispersant is firmly adsorbed on the particle surface and does not desorb; charge provides a strong electrostatic repulsion force to resist electrolyte interference; and steric hindrance forms a physical barrier to prevent particles from approaching each other. All three are indispensable and work together to achieve efficient and stable dispersion of nano-lithium iron phosphate.
[0023] Adaptability to nano-lithium iron phosphate: The dispersant of this invention is particularly suitable for nano-lithium iron phosphate batteries, achieving the characteristics of high specific surface area, non-agglomeration, and high requirements for dispersant adsorption capacity.
[0024] It has the advantage of wide temperature range performance: This invention not only achieves high dispersion efficiency at room temperature, but also exhibits excellent capacity retention under low temperature (-20℃) and high temperature (90℃) conditions. This is a direct beneficial effect brought about by the "triple synergy" mechanism, which is an effect that general-purpose dispersants cannot achieve. Attached Figure Description
[0025] Figure 1 The resistivity test curve of the electrode prepared in Example 2 of the present invention; Figure 2 This is a comparison chart of the fineness of the slurries prepared in Comparative Example 1 and Example 2; Figure 3 The room temperature capacity discharge curves of batteries from Comparative Example 2 and Examples 3-5 are shown. Figure 4 The discharge curves of the batteries in Comparative Example 2 and Examples 3-5 at 3C rate at room temperature are shown. Figure 5 The capacity retention rate of batteries in Comparative Example 2 and Examples 3-5 after charge-discharge cycles at 3C rate is shown in the graph. Figure 6 The capacity retention rate of the batteries in Comparative Example 2 and Examples 3-5 after being placed at -20°C for 5 hours and discharged at a 1C rate to 1.5 V; Figure 7 The capacity retention rate of the batteries in Comparative Example 2 and Examples 3-5 after being placed at 90°C for 5 hours and discharged at a 1C rate to 1.5 V was determined. Detailed Implementation
[0026] The following detailed description illustrates the specific implementation method: Example 1: Dispersant suitable for wide-temperature-range nano-lithium iron phosphate cathode slurry and its preparation method: Dissolve 6g IAI and 23g AMPS in 50g water and stir until completely dissolved. Adjust the pH to 3-4 (sulfonic acid groups are more stable in weak acid conditions for polymerization). Heat to 70℃ (to avoid pyrolysis of AMPS). Add a mixed solution of 45g MPEG-AA and 1.1g APS dropwise over 2.5h, and maintain the temperature for 4.5h. After the reaction is complete, neutralize the pH to 6-7 with an appropriate amount of NaOH solution. Sulfonic acid dispersants exhibit the best charge stability under neutral conditions. The final product is a light brown transparent dispersant solution with a solid content of 32%.
[0027] Example 2: Lithium iron phosphate cathode and its preparation method: Conductive agents can build a stable conductive network within the electrode, thereby improving the conductivity of the active material and the cycle stability of the battery. They can fill the gaps between active materials and enhance the contact between active substances and current collectors. SP is a nanoscale zero-dimensional conductive carbon particle that can only be dispersed on the surface of LFP particles, thus only a portion of the cathode particles contact it. CNTs are micron-scale one-dimensional tubular conductive agents that can form long-range conductivity. Graphene has a large specific surface area, good electronic and ionic conductivity, and can make good contact with active materials. Therefore, this invention combines the structural characteristics of SP, CNTs, and graphene to construct a three-dimensional composite conductive agent structure in the electrode. This combination of point, line, and surface advantages creates a synergistic effect, simultaneously establishing both "long-range" and "short-range" conductive networks within the electrode to improve its electrochemical performance.
[0028] Specifically, the positive electrode of this patent is prepared according to the formulation shown in Table 1 below, and the following operating steps are performed:
[0029] (1) Glue preparation: Weigh 2.5% of the total weight of PVDF into NMP, first stir at a low speed of 35 rpm and 500 rpm for 15 min, then stir at a medium speed of 45 rpm and 2000 rpm for 90 min until completely dissolved. During stirring, turn on the circulating water and vacuum, and disperse the glue on the stirring paddle as needed; (2) Add the dispersant solution from Example 1: Weigh 0.6% of the total weight of the dispersant solution into a stirrer and stir at 3500 rpm for 10 minutes at a revolution speed of 65 rpm. During high-speed stirring, turn on the circulating water and apply a vacuum. (3) Add conductive agent 1: Weigh 1.2% of the total weight of SP into a stirrer, first stir at a low speed of 35 rpm and 500 rpm for 30 min, then stir at a high speed of 65 rpm and 3500 rpm for 30 min. During high-speed stirring, turn on the circulating water and apply a vacuum. (4) Add conductive agent 2: Weigh 0.3% of the total weight of single-walled carbon nanotube slurry (calculated based on the solid content of carbon nanotubes) into a stirrer, and stir at a high speed of 3500 rpm for 30 min with a revolution of 65 rpm. During high-speed stirring, turn on the circulating water and apply a vacuum. (5) Add positive electrode active material: Weigh 95.4% of the total weight of LFP and add it in at least two batches. First, stir at a low speed of 35 rpm and 500 rpm for 60 min, then stir at a high speed of 65 rpm and 3500 rpm for 60 min until completely mixed. Observe the state of the slurry during stirring and add NMP as needed. Turn on the circulating water and vacuum during high-speed stirring. (6) Viscosity adjustment: Add an appropriate amount of NMP with a solid content of 58% according to the state of the slurry, and stir at a speed of 65 rpm and 3500 rpm for 30 min. During stirring, turn on the circulating water and vacuum. (7) Defoaming: Stirring speed 35 rpm, no dispersion, time 20 min; (8) Sieving the slurry: Sieve through a 150-mesh sieve and set aside for use; (9) Coating.
[0030] Example 3: Application Example: A single-cell battery is prepared using the positive electrode sheet obtained in Example 2: The positive electrode obtained in Example 2 was designed and matched with the graphite negative electrode. After baking, rolling and die cutting, the electrode was assembled into a stacked cell. After vacuum baking, the cell was packaged with aluminum-plastic film. Subsequently, electrolyte was injected in a dry room with humidity less than 3% RH. After the electrolyte completely wetted the cell, the battery was sealed. After the aging process and formation process, vacuum double sealing and other operations were performed to assemble it into a single cell. The separator used in the battery is a double-sided ceramic separator, and the electrolyte is 1 mol / L LiPF6 / EC+EMC+DMC (volume ratio = 1:1:1).
[0031] Example 4 differs from Example 3 in that the dispersant solution used is as follows: 9g of IAI and 25g of AMPS are dissolved in 40g of water and stirred until completely dissolved. The pH is adjusted to 3-4 (sulfonic acid groups are more easily stabilized for polymerization under weak acidity). The temperature is raised to 70℃ (to avoid pyrolysis of AMPS). A mixed solution of 48g of MPEG-AA and 1.2g of APS is added dropwise over 4 hours, and the temperature is maintained for 3.5 hours. After the reaction is complete, the pH is neutralized to 6-7 with an appropriate amount of NaOH solution. Sulfonic acid dispersants exhibit optimal charge stability under neutral conditions, resulting in a light brown transparent dispersant solution with a solid content of 35%.
[0032] Positive electrode configurations are as follows:
[0033] The solid content of NMP is 53%.
[0034] Example 5 differs from Example 3 in that a different dispersant solution is used: 6g of IAI and 28g of AMPS are dissolved in 50g of water and stirred until completely dissolved. The pH is adjusted to 3-4 (sulfonic acid groups are more easily stabilized for polymerization under weak acidity). The temperature is raised to 70°C (to avoid pyrolysis of AMPS). A mixed solution of 42g of MPEG-AA and 1.5g of APS is added dropwise over 3.5 hours, and the temperature is maintained for 4 hours. After the reaction is complete, the pH is neutralized to 6-7 with an appropriate amount of NaOH solution. Sulfonic acid dispersants exhibit optimal charge stability under neutral conditions, resulting in a light brown transparent dispersant solution with a solid content of 30%.
[0035] Different positive electrode ratios:
[0036] The slurry has a solids content of approximately 56%.
[0037] Comparative Example 1: The difference from Example 2 is that no dispersant or corresponding steps are added, while the other steps and parameters are the same.
[0038] Comparative Example 2: The difference from Example 3 is that the positive electrode obtained in Comparative Example 1 was used, while the other steps and parameters were the same.
[0039] The test results are shown in Table 2 below:
[0040] Depend on Figure 1 It can be seen that when the pressure gradually increases to 30 MPa, the electrode resistivity can drop to less than 1 / 7 of its original value. This indicates that the process overcomes the limitation of low intrinsic conductivity in the lithium iron phosphate system, and the three-dimensional conductive network forms a highly efficient conductive path. This results in a battery with low internal resistance and good electrochemical performance potential.
[0041] like Figure 2As shown, the slurry fineness prepared in Example 3 differs from that in Comparative Example 2 (which did not include a dispersion). The slurry fineness in the Comparative Example was approximately 35 μm, indicating that uneven dispersion during stirring led to particle agglomeration, which may result in unstable contact and connection of the subsequent electrodes, a poor conductive network, and reduced electrochemical performance of the battery. In contrast, the slurry fineness in Example 3 was below 15 μm, demonstrating the effectiveness of this dispersion with its triple synergistic effect of "anchoring-charge-steric hindrance." The conductive agent and binder in the slurry were fully dispersed, and the soft agglomerates between the nano-lithium iron phosphate particles were largely broken up, forming a continuous and dense conductive network that ensured unobstructed electron transport paths. This also corresponds to the resistivity results mentioned above. Furthermore, this demonstrates the rationality of the formulation design, the optimization of the slurry preparation process, and the effectiveness of the dispersion equipment and parameters.
[0042] like Figure 3 As shown in the room temperature capacity discharge curves of the comparative example and the embodiment, the capacity of the comparative example discharged at 1C rate at room temperature is 2.091 Ah, while the highest discharge capacity of embodiment 3 reaches 2.199 Ah. This indicates that the partial agglomeration of the positive electrode material in the comparative example slows down the lithium-ion diffusion rate, preventing sufficient charging and discharging, thus resulting in a lower discharge capacity. The slurry in the embodiment, however, exhibits higher dispersion uniformity and stability, achieving low internal resistance and high conductivity in the battery electrode, effectively improving the battery's discharge capacity.
[0043] like Figure 4 As shown, the discharge curves of the comparative and example batteries at room temperature and a 3C rate reveal that the discharge capacity of the comparative battery is 1.991 Ah, while the discharge capacity of the example batteries is comparable, with Example 3 reaching 2.137 Ah. These figures represent capacity retention rates of 95.21% and 97.18% respectively at 1C discharge. While the polarization voltage decreases slightly after a 3-fold increase in discharge rate, the discharge capacity after the triple synergistic effect of "anchoring-charge-steric hindrance" is almost identical to the discharge capacity at 1C, achieving a balance between high capacity and high power. This result exceeds the requirement of >90% capacity retention at high-rate discharge for power batteries in the national standard GB / T 31486. This is attributed to the more uniform distribution of active materials, conductive agents, and binders in the slurry after the addition of the composite dispersion, resulting in an excellent three-dimensional conductive network and a stable electrode structure.
[0044] like Figure 5As shown in the capacity retention graphs of the comparative and example batteries after charge-discharge cycles at 3C, the capacity retention rates of the comparative and example batteries after 500 cycles are over 84.3% and 94.4%, respectively. This indicates that the slurry in the example achieves a triple synergistic effect of "anchoring-charge-steric hindrance." This triple synergistic dispersion promotes a uniform and stable electrode microstructure, effectively suppressing the pulverization and shedding of active particles and the destruction of the conductive network during long-term cycling. Consequently, after 500 cycles, the capacity decay rate of the example is only about one-third that of the comparative example, demonstrating a significant improvement in battery life.
[0045] from Figure 6 It can be seen that after being placed at a low temperature of -20°C for 5 hours, the discharge capacities of the comparative and example batteries discharged at a 1C rate to 1.5 V were approximately 1.543 Ah and 1.795 Ah, respectively, with a discharge capacity retention rate of 73.79% and 83.60% relative to the 1C discharge at room temperature. The low-temperature capacity retention rate of the example after adding the composite dispersion was improved by about 10%, indicating that the dispersed cathode material fully utilized its capacity.
[0046] from Figure 7 It can be seen that after being placed at a low temperature of 90°C for 5 hours, the discharge capacities of the comparative and example batteries discharged at a 1C rate to 1.5 V were approximately 1.988 Ah and 2.145 Ah, respectively, with a discharge capacity retention rate of 95.07% and 97.52% relative to the 1C discharge capacity at room temperature. This further demonstrates that the uniform and stable electrode structure constructed by adding the composite dispersion not only facilitates ion / electron transport but also effectively suppresses side reactions at high temperatures.
[0047] The above descriptions are merely embodiments of the present invention, and common knowledge such as specific technical solutions and / or characteristics are not described in detail here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the technical solutions of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the implementation of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.
Claims
1. A dispersant suitable for wide-temperature-range nano-lithium iron phosphate cathode slurry, characterized in that, The dispersant comprises a ternary dispersant and an initiator consisting of itaconic acid imine, 2-acrylamide-2-methylpropanesulfonic acid and methoxy polyethylene glycol acrylate.
2. The dispersant for wide-temperature-range nano-lithium iron phosphate cathode slurry according to claim 1, characterized in that, The initiator is ammonium persulfate.
3. The dispersant for wide-temperature-range nano-lithium iron phosphate cathode slurry according to claim 2, characterized in that, By weight fraction, the itaconic acid imine is 6-9 parts, 2-acrylamide-2-methylpropanesulfonic acid is 22-28 parts, methoxy polyethylene glycol acrylate is 42-52 parts, and ammonium persulfate is 1-1.5 parts.
4. The dispersant for wide-temperature-range nano-lithium iron phosphate cathode slurry according to claim 3, characterized in that: The dispersant is a light brown transparent solution with a solid content of 28% to 35%.
5. A method for preparing the dispersant according to any one of claims 1 to 4, characterized in that, Itaconic acid imine and 2-acrylamide-2-methylpropanesulfonic acid are dissolved in water and stirred until completely dissolved. The pH is adjusted to 3-4, and the temperature is raised to 65-75°C. Then, a mixed solution of methoxy polyethylene glycol acrylate and ammonium persulfate is added dropwise. After the reaction is completed, the pH is adjusted to 6-7 to obtain the dispersant.
6. The method according to claim 5, characterized in that: When adding a mixed solution of methoxy polyethylene glycol acrylate and ammonium persulfate, the adding time should be controlled to be 2.5~3.5h.
7. The method according to claim 6, characterized in that: The solution used to adjust the pH to 6-7 is a 15% NaOH solution.
8. The application of the dispersant according to any one of claims 1 to 4 in the preparation of nano-lithium iron phosphate battery cathode slurry.
9. A positive electrode slurry, characterized in that... Includes the dispersant as described in any one of claims 1 to 4.
Citation Information
Patent Citations
Dispersant for lithium ion battery and preparation method thereof, positive electrode slurry, positive electrode sheet and lithium ion battery
CN114583163B